Sets of independent vectors in spaces of unlimitedly growing dimensionality - Stepakhno , V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We study a region of a space in which are concentrated independent observations of random vectors if the dimension of the space and the number of observations approaches infinity, and the distribution function of the components ξki of the observed vectors does not depend on n or m and satisfies the conditions: 1) it is continuous and symmetric: F (х) = 1 — F (—x); 2) its tails are slowly varying functions.